R Rancang bangun game edukasi fisika berbasis android pada materi suhu dan kalor : Rancang Bangun Game Edukasi Fisika berbasis android pada materi suhu dan kalor - Firdaus Firdaus; Alrizal; M. Furqon; M. Feby Khoiru Sidqi (PendIPA Journal of Science Education, 2023)
The aim of this study was to develop an android based physics educational game on temperature and heat material using the construct 2 program, where the game was designed to stimulate thinking ability including improving understanding of physics concepts. This educational game was developed using the research and development (R&D) method with the stages of the ADDIE model, namely analysis, design, development, implementation and evaluation, but in this study it only reached the design or development stage. In addition, to ensure that the game is designed as expected, the authors conducted feasibility testing and game acceptance by media experts and students. Based on the results of the analysis, the assessment obtained from 5 experts with several aspects of assessment of this educational game is included in the very feasible category with an average score of 3.70 from a maximum score of 4.00 and a minimum score 3.0. From the results obtained, the physics educational game developed has good quality so it is feasible to be implemented.